Motivação, mulheres e forças armadas: incentivos que impulsionam mulheres a ingressarem no exército brasileiro - (:unkn) unknown (Universidade Federal do Pampa, 2016)
This qualitative study has as objective analyze the reasons that make women join the Brazilian Army and relate them with the Theory of the Hierarchy of the Necessities of Abraham Maslow. To reach the objective a bibliographical research was performed concerning motivation, of the Theory of Maslow, about the feminine presence in World War II and the trajectory of the Brazilian women in the Armed Forces. Also interviews were performed with five women from two units of the Brazilian Army of the city of Santana do Livramento. The results show that the reasons for the interviewed women choose the military profession are related to the stability that the profession provides and not to the factor “self-realization” that was expected to be found before the accomplishment of the interview. It could be concluded that the motivational factor is related to the second slice of the Pyramid of Maslow. Where it is find the necessity of security. It is expected that with this study contribute to the advance of research related to the feminine presence inside of military institutions
Motivation, women and armed forces: incentives that promote women to enter the Brazilian Army
Keywords: Public management: Brazil; Woman; Brazilian Army: female enlistment; Motivation; Gestão pública: Brasil; Mulher; Exército Brasileiro: alistamento feminino; Motivação